Merwin’s Prose Poetry: Collective Memory in Uncanny Short Fiction - Françoise Palleau-Papin (Transatlantica)
In his early collections of short fiction pieces in prose poetry, The Miner’s Pale Children (1970) and Houses and Travellers (1977), W.S. Merwin exposes the discrepancies between the past and the present in the lack of connection between generations, as well as between mankind and nature across time. His explorations of such disconnections make use of an array of literary means to express the uncanny resurgences of the past as a haunting figure in a collective unconscious, once memory and a sense of inheritance have been lost or damaged. Using syntax and repetition to suggest the repressed in prose poetry, and borrowing from several literary traditions such as a revised allegorical storytelling, Merwin emphasizes the memory loss by giving it a puzzling form. In so doing, he manages to invite readers to connect the pieces of an unsettling world to make sense of the irretrievable, in a joint effort to read the loss as collective rather than personal.